2015
DOI: 10.1210/en.2015-1042
|View full text |Cite
|
Sign up to set email alerts
|

Teleocortin: A Novel Member of the CRH Family in Teleost Fish

Abstract: The CRH family of neuropeptides, including CRH and urocortins, plays pivotal roles in the regulation of physiological and behavioral stress responses in vertebrates. In this study, we identified a previously undescribed member of the CRH family of peptides in a teleost fish species (medaka; Oryzias latipes) and named this peptide teleocortin (Tcn). Medaka Tcn is a 41-amino acid polypeptide derived from the C terminus of a larger precursor protein that is encoded by a 2-exon gene, thus sharing common structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…However, CRH2 was lost in placental mammals and in teleost genomes. We also confirm by synteny and paralogon analysis that the recently reported CRH-related peptide in teleost fish, named teleocortin and proposed to be an ancestral vertebrate duplicate (Hosono et al 2015), is in fact a teleost-specific gene copy of CRH that arose in the teleost tetraploidization, as recently reported (Grone & Maruska 2015a). The evolutionary implications of this ancient ancestral complexity of the CRH system are discussed.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, CRH2 was lost in placental mammals and in teleost genomes. We also confirm by synteny and paralogon analysis that the recently reported CRH-related peptide in teleost fish, named teleocortin and proposed to be an ancestral vertebrate duplicate (Hosono et al 2015), is in fact a teleost-specific gene copy of CRH that arose in the teleost tetraploidization, as recently reported (Grone & Maruska 2015a). The evolutionary implications of this ancient ancestral complexity of the CRH system are discussed.…”
Section: Introductionsupporting
confidence: 85%
“…After completion of this study, a member of the CRH peptide family was reported in a few species of teleost fish and was named teleocortin (Tcn) (Hosono et al 2015). The gene was reported to be missing in zebrafish.…”
Section: Lineage-specific Differences In Crh Family Evolutionmentioning
confidence: 99%
“…In the latter, two crh ohnologs, named crha and crhb, have been identified (Grone and Maruska, 2015). The expression of crha has been mainly observed in the retina (Grone and Maruska, 2015;Hosono et al, 2015), with weak expression in the brain (about 100 times less than in retina) (Hosono et al, 2015), in fish. By contrast, crhb is mainly expressed in the central nervous system (CNS), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The action of Crh in the pituitary is mediated by the binding and activation of two highly conserved membrane receptors (Crhr1 and Crhr2), which belong to class B of the G protein-coupled receptors (Lovejoy et al, 2014). Although in tetrapods, it has been reported that Crh has higher affinity for Crhr1 (Vaughan et al, 1995), in teleosts both Crh ligands have similar affinity for both Crh receptors (Hosono et al, 2015). Several studies in mammals have also demonstrated the ability of Crh receptor antagonists to block stress responses, such as anxiety or depression (Backström and Winberg, 2013;Grammatopoulos and Chrousos, 2002;Holsboer and Ising, 2008), placing Crh receptors at a crucial point in regulation of the HPA axis.…”
Section: Introductionmentioning
confidence: 99%
“…Although crfa was only recently identified, the results of Grone and Maruska (35) suggest that the expression patterns of crfa in teleosts are species-specific. Therefore, although the dominant cardiac mRNA levels of crfa in zebrafish is consistent with the high expression levels of teleocortin (an ortholog of zebrafish crfa) in the heart of medaka (37), further studies may be needed to confirm whether CRFa is the dominant cardiac CRF ligand in teleost fish.…”
Section: Discussionmentioning
confidence: 91%